Simultaneity and aggregation of risk factors for noncommunicable diseases among brazilian adolescents - Fabiana Lucena Rocha; Gustavo Velasquez-Melendez
Abstract Objective: To estimate the prevalence of concurrency of risk factors for Noncommunicable Diseases and non-random aggregation of these in Brazilian school adolescents. Method: Descriptive study, with data from the National School Health Survey (Pesquisa Nacional de Saúde do Escolar), 2015. The prevalence of concurrent risk factors was estimated: smoking, alcohol use, physical inactivity and low consumption of fruits and vegetables. Aggregation was verified when the observed-expected prevalence ratio was greater than 1. The analyses were performed in Stata 15.0 software. Results: The proportion of concurrent risk factors was higher for those who had two risk factors (56.1%; 95%CI: 55.5-56.6). The most prevalent risk factors combination was "Low consumption of fruits and vegetables + Physical inactivity" (66%; 95% CI: 65.8-66.9). There was an aggregation of risk factors, and the highest ratio between observed and expected prevalence was: "Smoking + Alcohol" (79.0%; 95%CI: 73.8-84.2). Conclusion and implications for practice: The findings show a high prevalence of concurrent risk factors, with aggregation of these in adolescents. Identifying these risk groups may favor early interventions by minimizing exposure and targeting primary prevention strategies in early exposure to risk factors.